Implementasi Pembelajaran Sejarah Berbasis Sumber Ajar Batik Tangerang (Studi Kasus: SMAN 3 Kabupaten Tangerang) - Rahayu Permana; Ahmad Bakhtiar; Nur Fajar Absor (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The culture of the people of Tangerang Regency, starting from hat crafts to Tangerang batik crafts, is one part of local wisdom. To preserve it so that it doesn't become extinct or disappear, it is necessary to carry out an activity in the preservation and introduction of various Tangerang batik motifs to the public, especially students who are in Tangerang Regency. Thus, the problem of maintaining local wisdom values in the typical Tangerang batik motifs is an important matter for Tangerang Regency. Therefore, in introducing various Tangerang batik motifs, it is necessary to introduce them to schools. So, that schools in Tangerang Regency care about preserving their local wisdom. The research method used is a qualitative method, while the data collection techniques used are observation, interview, and documentation. The research results are (1) there is a need for an introduction to local history based on the local wisdom values of Tangerang batik, because it will add local insight to students at SMAN 3 Kabupaten Tangerang; (2) the implementation of history learning on Tangerang batik craft material motivates students, because it is taught by history teachers who have prepared the learning process, both from lesson plans, materials, methods, and media specifically; and (3) the obstacles found in learning, namely the availability of material that is not widely available in the school library and the time allocation that is not sufficient to discuss broader material in learning local history.